STRATEGY FOR ACCELERATING DIGITAL TRANSFORMATION ON THE FINANCIAL PERFORMANCE OF PT TELEKOMUNIKASI INDONESIA (PERSERO) TBK. - Heni Risnawati; Sukma Wijayanti (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
The purpose of this research is to see the financial performance of PT. Telekomunikasi Indonesia (Persero) Tbk for the period 2016-2020. Ratio analysis used liquidity ratios, solvency ratios, activity ratios and profitability ratios. This study uses secondary data by analyzing the company's annual report. The data analysis method in this research is descriptive statistical analysis which is used to explain the company's financial ratios. The results of the liquidity ratio analysis with the Current Ratio indicator have an average value of 90.76% below the industry standard average of 200%. Quick ratios and cash ratios have values below the industry average standard. This shows that the company is not performing well. The solvency ratio with the Debt Ratio indicator on average is 44.9% above the industry average standard of 35%. The company's performance is still in the quite good category, although it is slightly above the industry average standard. The Debt to Equity Ratio indicator on average is 83.2% above the industry average standard of 90%. This shows the performance of Pt. Telekomunikas Indonesia Tbk has a good performance. The activity ratio is measured with the working capital ratio indicator on average 20.9% above the industry average standard, meaning the company has a good performance. The Total Assets Turn Over indicator is on average 0.59 miles below the industry average 2 times. This shows that the company's performance is not good. The profitability ratio through the Net Profit Margin indicator is an average of 22.9% above the industry average standard of 20%. The Return On Investment indicator is on average 13.5% below the industry average of 30%company's performance is in poor condition. Keywords: Financial performance, liquidity, solvency, activities, profitability, digital transformation